Minangkabau Cultural Values Cultivating Strategy in the Minang Perantau Family in Bandung City - Ernawati Ernawati; Achmad Hufad; Wilodati Wilodati (Postgraduate School, Universitas Negeri Padang, 2021)
This research reveals how the strategy in cultivating Minangkabau cultural values in the Minang Migrant family in Bandung City. The method used in this study using a literature study that analyzed a variety of studies relevant to the value investment strategy cultural studies Minangkabau. The presentation of the data is carried out using descriptive techniques, namely describing the strategy of cultivating Minangkabau cultural values in Minang nomadic families in Bandung. The results of this study point to the right strategy cultivating cultural values Minangkabau in Minang nomadic families in the city of Bandung, namely: 1) Providing examples and role models from parents; 2) Actuating their wedding ceremony customarily Minang pure; 3) Supporting them participate Minang activities; 4) Performance culture: Minang sing, dance Minang, Silek Minang, traditional food, and traditional clothing Minang; 5) Coming Home West Sumatra within a certain time so that children can see the beauty of the natural beauty and culture of West Sumatra Minangkabau, kampong can see the customs, art, and culture.